Relationship Of Risk Factors For Hypertension In Pregnant Women In Indonesia: Literature Riview - Aprida, Cantika Dewi Berliana; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
Hypertension during pregnancy is a common and leading cause of maternal death and other serious consequences during childbirth. Hypertension during pregnancy occurs in 5% of all pregnancies. Risk factors for hypertension in pregnant women include (1) the relationship between the degree and the incidence of hypertension during pregnancy, (2) the relationship between body mass index and the incidence of hypertension during pregnancy, and (3) age and the incidence of hypertension during pregnancy. Relationship of hypertension (4) History of childbirth and hypertension of pregnancy (5) History of hypertension and hypertension of pregnancy. The method used in this research is literature study by reviewing or reviewing existing information or processing research materials. The number of gestational hypertension in Indonesia is increasing and almost 30% of maternal deaths in Indonesia are caused by gestational hypertension which is one of the main causes of maternal death after bleeding in Indonesia. Pregnant women are expected to avoid risk factors that can increase the incidence of hypertension during pregnancy, and health practitioners are encouraged to help pregnant women avoid risk factors at an early age. to pregnant women. What causes high blood pressure.